AN IDIOMATIC EXPRESSION ANALYSIS ON AN AUTHENTIC MATERIAL “PRIDE AND PREJUDICE MOVIE” A MOVIE FROM JANE AUSTEN BOOK - Kurniasy, Dessy; Sonia, Eka (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2020)
The study was aimed to find and analyzed about how many idiom consist in Pride and Prejudice (2005) Movie, what are the meanings of idiom in Pride and Prejudice (2005). The data was taken from dialog line of the actor and actresses in the Pride and Prejudice (2005) where it was the script of the movie. Research design in this study was descriptive qualitative research. The technique used by the writer to collect the data was documentation. The finding showed that there are four classifications of idiom according to the Moon in Mabruroh (2015); those are transparent idioms, semi-transparent idioms, semi-opaque idioms, and opaque idioms. Transparent idioms are those idioms which are easy to comprehend its constituent meaning. Semi-transparent idioms are the idioms that usually have metaphorical meaning and their constituent parts have a little role in comprehending the whole meaning of the expression. Semi-opaque idioms are the group of idioms whose figurative meaning is not related to the meaning of their constituent words, in other words, the idiomatic expression is separated into two parts; a part with literal meaning, and the other part with a figurative meaning. The last is opaque idioms which is the idioms where the literal meaning of their parts have little to do with actual sense of idiom because it has cultural reference item. Transparent idioms that has been found in the movie is about 25 idioms, semi-transparent idioms is about 20 idioms, whether semi-opaque idioms are found about 17 idioms and the last, opaque idioms that has been found in the movie is about 18 idioms.